Placental Protein 13 (Galectin-13) Polarizes Neutrophils Toward an Immune Regulatory Phenotype - Vokalova, Lenka; Balogh, Andrea; Toth, Eszter; Van Breda, Shane V.; Schäfer, Günther; Hoesli, Irene; Lapaire, Olav; Hahn, Sinuhe; Than, Nandor Gabor; Rossi, Simona W. (Frontiers in Immunology, 2020)
Termed as galectin-13, placental protein 13 (PP13) is exclusively expressed in the placenta of anthropoid primates. Research on PP13 in normal and pathologic pregnancies show alteration of PP13 concentrations in pregnancy affected by preeclampsia or gestational diabetes. Galectins are also described as potent immunomodulators, and PP13 regulates T cell function in the placenta. Therefore, this study aims to investigate the effects of PP13 on neutrophils; a cell type often ignored in pregnancy, but present in the uterus and placenta from the early stages of pregnancy. Since neutrophil function is dysregulated during pathologic pregnancies, a link between PP13 and neutrophil activity is possible. We determined that PP13 reduces the apoptosis rate in neutrophils. Also, PP13 increases the expression of PD-L1 and production of HGF, TNF-, reactive oxygen species (ROS), and MMP-9 in these cells. This phenotype resembles one observed in permissive tumor neutrophils; able to sustain tissue and vessel growth, and inhibit T cell activation. At the same time, PP13 does not alter all neutrophil functions, i.e., extrusion of neutrophil extracellular traps, degranulation, phagocytosis, and ROS production following bacterial exposure. PP13 seems to play an essential role in regulating the activity of neutrophils in the placenta by polarizing them towards a placental-growth-permissive phenotype.